Análise da produção e comercialização de mel natural no Brasil no período de 1999 a 2010 - Pasin, Luiz Eugênio Veneziani; Tereso, Mauro José Andrade; Barreto, Lídia Maria Ruv Carelli [UNESP] (My University, 2012)
The aim of this study was to analyze the evolution of natural honey production in Brazil, as well as the Brazilian performance in the international markets and their own consumption behavior of natural honey in the domestic market. For this study, we used descriptive analysis of time series information, data production and export of natural honey understood, respectively, for the periods 1999 to 2010. To analyze the correlation between the series of apparent consumption per capita (variable X) and the international price data (variable Y), we used the statistical analysis of the correlation coefficient of Pearson (CP). Main results revealed that the Brazilian production of natural honey has more than doubled in the last decade, while the Northeast region was the largest contributor to this performance. This increase in the production was mainly directed towards supplying the international market, which currently consumes more than half of Brazilian production. It is true that the change in the international market price has a direct effect on domestic supply, but the Brazilian domestic market has potential for increasing effective consumer who deserves to be better exploited; it implies to pay attention to the supply of quality natural honey, quantity and regularity.
Analysis of production and sale of the natural honey Brazil in the period from 1999 to 2010
Keywords: Beekeeping; Brazil; Consumer market; Marketing; Natural honey; Production